Self Efficacy and Barriers to Smoking Cessation in Men and Women in Medan: Case Study in the Lower Class Economic Community - Miskah Afriani; Asrul; Wahyuni; Makhfura Syukrillah (Pena Cendekia Insani, 2021)
Self-efficacy is an important factor in quitting smoking. The goal of this study was to describe the self-efficacy of quitting smoking and to investigate the factors that contribute to smoking cessation in low-income communities with pedicab drivers and traders working on the outskirts of Medan City. This study took an exploratory research approach, with data collected first through a questionnaire and then through additional interviews. The SSQ, which has been standardized in Indonesian, is used for interview guidance, and expert validity is used. The study included 39 people (32 men and 7 women) who worked as pedicab drivers and market vendors. The results showed that low self-efficacy was 15.3%, smokers with low self-efficacy had barriers to smoking cessation dominated by the mastery experience factor (56.4%). Barriers to quitting smoking are due to mastery experience, namely weak intentions and failure to learn from one's own experience. While the barriers to vicarious experience are due to the factor of seeing a peer group that remains healthy and happy because of smoking. Meanwhile, verbal persuasion is caused by a friend's invitation to women, while men are afraid of getting a bad image. Low self-efficacy was 15.3 percent, sufficient self-efficacy was 61.6 percent, and high self-efficacy was 23.1 percent, according to the findings. The mastery experience factor dominates the barriers to quitting smoking in smokers with low self-efficacy (56.4 percent ). It is hoped that the suggestions in this study will help smokers develop a strong will and a strong belief that they can quit smoking. It is also recommended that psychoeducation and counseling approaches be used to help people quit smoking.